2006
DOI: 10.1149/1.2240085
|View full text |Cite
|
Sign up to set email alerts
|

Initial Testing of Solutions to Redox Problems with Anode-Supported SOFC

Abstract: The most commonly used solid oxide fuel cell (SOFC) anode material is a two phase nickel- and yttria-stabilized zirconia (Ni/YSZ) cermet. During typical fuel cell operation, this material remains a cermet; however, in a commercial SOFC system seal leakage, fuel supply interruption, or other situations may cause the anode to reoxidize. The cyclic reduction and oxidation (redox) of nickel results in large bulk volume changes, which may have a significant effect on the integrity of interfaces within the fuel cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…The authors concluded that there is an optimum composition and microstructure for substrates and anodes which yield a minimum redox strain and lead to mechanical degradation. Considering the various approaches in this field and to some extent inconsistent results, further investigations on optimizing the microstructure are required [1,9]. The influence of particle sizes, particle size ratios, porosity, and pore size distribution and composition on the redox tolerance of substrates and anodes has yet to be clarified as does the potential for a technological solution of the redox problem by optimizing the microstructure.…”
Section: Influence Of the Microstructurementioning
confidence: 99%
See 2 more Smart Citations
“…The authors concluded that there is an optimum composition and microstructure for substrates and anodes which yield a minimum redox strain and lead to mechanical degradation. Considering the various approaches in this field and to some extent inconsistent results, further investigations on optimizing the microstructure are required [1,9]. The influence of particle sizes, particle size ratios, porosity, and pore size distribution and composition on the redox tolerance of substrates and anodes has yet to be clarified as does the potential for a technological solution of the redox problem by optimizing the microstructure.…”
Section: Influence Of the Microstructurementioning
confidence: 99%
“…The reoxidized nickel can be re-reduced, but various investigations have revealed that the structure of substrate and anode cannot be restored [2][3][4][5][6][7][8]. The structural changes in the substrate and anode upon reoxidation lead to dimensional changes that generate stresses in substrate, anode and other cell components, potentially promoting damage in all layers of the cell and therefore degrading cell performance or even causing complete failure of the cell [1,3,5,6,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been shown that some improvement of the redox stability is possible by optimisation of the microstructure [3,8,9], it remains a challenge to construct an anode cermet that is really tolerant to redox cycling. Especially for anode supported cells, tensile stresses associated with the expansion of the substrate due to nickel oxidation are often accomodated by cracks in the electrolyte and cathode layer, which leads to gas cross-over and thereby efficiency loss, and efforts to improve the redox tolerance had only limited success [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Maintenance solutions to the redox cycling problem currently include purging with N 2 gas, but this is not always feasible in remote locations [12]. System solutions to the redox cycling problem are generally very costly due to the high operating temperature [13,14], are being investigated, no Ni-free anodes have yet been proven to be adequate in terms of performance or longterm operation.…”
Section: Introductionmentioning
confidence: 99%